Eocene Antarctica: a window into the earliest history of modern whales. - Buono, Mónica Romina; Fordyce, Robert Ewan; Marx, Felix E.; Fernández, Marta Susana; Reguero, Marcelo Alfredo
The Eocene–Oligocene Southern Ocean is thought to have played a major role in cetacean evolution. Yet, fossils from its heart – Antarctica – are rare, and come almost exclusively from the Eocene La Meseta and Submeseta formations of Marambio (Seymour) Island. Here, we provide a summary and update of this crucial fossil assemblage, and discuss its relevance in the broader context of cetacean evolution. To date, Eocene specimens from Antarctica include basilosaurids, a group of archaic stem cetaceans that had already fully adapted to life in water; and the archaic toothed mysticete Llanocetus , the second oldest crown cetacean on record (ca. 34 Ma). This Eocene co-occurrence of stem and crown cetaceans is highly unusual, and otherwise only observed in Peru. Though related, at least some of the Antarctic species appear to be different from, and notably larger than their Peruvian counterparts, suggesting an early differentiation of the high latitude cetacean fauna. Fil: Buono, Mónica Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto Patagónico de Geología y Paleontología; Argentina Fil: Fordyce, Robert Ewan. University of Otago; Nueva Zelanda. National Museum of Natural History; Estados Unidos Fil: Marx, Felix E. Université de Liège; Bélgica. Monash University; Australia Fil: Fernández, Marta Susana. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina